1989
DOI: 10.1507/endocrj1954.36.515
|View full text |Cite
|
Sign up to set email alerts
|

Possible Hyperaldosteronism and Discrepancy in Enzyme Activity Deficiency in Adrenal and Gonadal Glands in Japanese Patients with 17 .ALPHA.-Hydroxylase Deficiency.

Abstract: We reviewed the pathophysiology of our previously reported female patient who had glucocorticoid-responsive hyperaldosteronism and was treated successfully with daily dose of dexamethasone (Dex) for 21 years. In this present study, the possibility that the patient may have 17 alpha-hydroxylase deficiency (17-OH-D) mainly in the adrenal could not be ruled out. We therefore reviewed 31 Japanese patients diagnosed as having 17-OH-D with suppressed plasma renin activity reported in Japan. Among these patients, 9 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Classically, suppressed renin is associated with low aldosterone in CYP17A1 deficiency. However, aldosterone levels have been detectable or even elevated in several other cases of CYP17A1 deficiency [2,35]. Cross-reactivity of other compounds in the aldosterone radioimmunoassay has been one proposed mechanism for this unexpected finding [5,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classically, suppressed renin is associated with low aldosterone in CYP17A1 deficiency. However, aldosterone levels have been detectable or even elevated in several other cases of CYP17A1 deficiency [2,35]. Cross-reactivity of other compounds in the aldosterone radioimmunoassay has been one proposed mechanism for this unexpected finding [5,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, aldosterone levels have been detectable or even elevated in several other cases of CYP17A1 deficiency [2,35]. Cross-reactivity of other compounds in the aldosterone radioimmunoassay has been one proposed mechanism for this unexpected finding [5,35]. However, Yamakita et al [35] repeated the measurement of aldosterone in 2 of their subjects using two different assays (albeit both radioimmunoassays) with similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic mecha nism of the high aldosterone levels in these patients is unknown. Interestingly Yamakita et al [21] have pointed out that Japanese cases with hyperaldosteronism showed a lower 17a-hydroxylase activity since these patients showed lower levels of serum cortisol and DHEA and a lower response of cortisol to ACTH stimulation. The authors have speculated that the lower the 1701-hydroxy lase activity the greater the increase of corticosterone methyloxidase II activity in the zona fasciculata.…”
Section: Discussionmentioning
confidence: 99%
“…indicated that the normal or increased aldosterone levels might be derived from cross-reaction in the aldosterone radioimmunoassay with other increased steroids such as DOC or corticosterone [2], such cross-reactions are generally considered to be minimal in the assay employed [20]. It has been suggested that continuously increased ACTH might stimulate aldosterone synthesis through the enhancement of P450 corticosterone methyloxidase activity which has been observed especially in cases of a marked decrease in serum cortisol and an associated increase in plasma ACTH [21]. It is noteworthy that the plasma aldosterone level in the present case decreased transiently below normal after dexamethasone administration along with the decrease in the plasma ACTH level and returned to normal subsequent to the increase in PRA.…”
Section: Endocrinological Examinationsmentioning
confidence: 99%